2006
DOI: 10.1007/s10653-005-9025-x
|View full text |Cite
|
Sign up to set email alerts
|

A study on cometabolic bioventing for the in situ remediation of trichloroethylene

Abstract: Cometabolic bioventing for removal of TCE in the unsaturated zone was studied in a soil column study using methane as growth substrate. A numerical model was developed for simulating the behavior of TCE during cometabolic bioventing. The model parameters were estimated independently through laboratory batch experiments or from the literature. Simulations were found to provide reasonable agreement with the experimental data. The experimental data show that a total TCE remediation efficiency of over 95% was obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Results indicated that optimum bioventing conditions were 18 wt.% soil water content, C:N = 10:1, using NH 4 ? - Sui et al (2006) have studied the cometabolic bioventing for removal of TCE in the unsaturated zone in a soil column study using methane as growth substrate, and the experimental data showed that a total TCE remediation efficiency of over 95% was obtained with a volatilization -to-biodegradation ratio of TCE being about 7:1.…”
Section: Bioventingmentioning
confidence: 99%
“…Results indicated that optimum bioventing conditions were 18 wt.% soil water content, C:N = 10:1, using NH 4 ? - Sui et al (2006) have studied the cometabolic bioventing for removal of TCE in the unsaturated zone in a soil column study using methane as growth substrate, and the experimental data showed that a total TCE remediation efficiency of over 95% was obtained with a volatilization -to-biodegradation ratio of TCE being about 7:1.…”
Section: Bioventingmentioning
confidence: 99%
“…In many cases, some of the key enzymes and cofactors responsible for transformation of the non-growth substrate and utilization of the obligated growth substrate are shared. Co-metabolism can be optimized by maintaining the proper ratio of growth to non-growth substrates (Jung and Park 2005;Kan and Deshusses 2006;Sui et al 2006;Claus et al 2007). Microbial co-metabolism of organic pollutants has drawn a great deal of attention because of its potential for high transformation rates, wide applicability to a broad range of compounds, and a requirement for an inexpensive and widely available primary growth substrate (Kim et al 2004;Frascari et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In real remediation projects in field, oxygen was provided to accelerate the aerobic metabolism, which is called bioventing. It was reported that the number of bacteria increased substantially during co-metabolic bioventing [20]; along with the enhancement in biodegradation, evaporation into ambient air will increase simultaneously. The changes in the two processes are not linear, and hence it is possible to select an optimized oxygen injection rate to achieve the maximum biodegradation rate at an acceptable evaporation rate.…”
Section: Resultsmentioning
confidence: 99%